HUBUNGAN PERCEIVED QUALITY DENGAN KEPUASAN FASILITAS KESEHATAN TINGKAT PERTAMA (FKTP) DI WILAYAH SURABAYA TIMUR PADA PELAYANAN BPJS KESEHATAN - Arinda Zahra Puspitasari; Erna Waty (Universitas Airlangga, 2018)
Primary health cares facility called as FKTP as partners of social health insurance organization called BPJS Kesehatan to provided basic health services. It is important to paid attention for FKTP satisfaction toward BPJS Kesehatan to optimized health services that gave to public. One of the factors that influence satisfaction is perceived quality, which is perception of services. The main purposed of this research is to analyze the correlation between satisfaction and perceived quality included professionalism and skills, attitude and behavior, accessibility and flexibility, reliability and truthworthiness, recovery, reputation and credibility. This research is an observational research with cross sectional design. Sample was determined by using the total population method involving 35 FKTP in East Surabaya area consisting of puskesmas and primary health clinic. This research used the primary data obtained from the questionnaire. The results of research shows that most FKTP is satisfied. The result of the correlation between variable reliability and trustworthiness; reputation and credibility with satisfaction is strong, attitudes and behavior; recovery with satisfaction is quite strong, and professionalism and skill; accessibility and flexibility with satisfaction is low. Needs improvement for recovery aspects about the existence of a fast and responsive complaint handling system with assignation BPJS Kesehatan employee in every FKTP for direct complaints handling that related to JKN-KIS program.